Structural characterization of Methanobactin using NMR and mass spectroscopy reveals a new chemical structure. - Behling, Lee A. (My University, 2008)
Methanobactin ia a small copper-sequestering molecule produced by the bacteria Methylosinus trichosporium OB3b. This research employed nuclear magnetic resonance (NMR) and mass spectroscopy to elucidate the structure of methanobactin when exposed to low levels of copper.
Structural characterization of Methanobactin using Nuclear Magnetic Resonance (NMR)
Color poster with text and diagrams describing research conducted by Lee Behling under the supervision of Warren Gallagher and Scott Hartsel.
Keywords: Chemical structure--Analysis.; Methanobactin--Effect of copper on.; Methanobactin--Structure.; Posters.